PECULIARITIES METHODS OF OPTIMIZATION CALCULATION OF PARAMETERS OF COMBINED SOLAR POWER PLANTS - J. M. Ibrokhimov (Journals Park Publishing, 2023)
This paper presents the types of combined devices, their appearance, methods of use, directions of use, and advantages in use. In addition, calculations of the optimization parameters of solar installations were considered.
Keywords: energy, solar flux, power, installation, combined system, photo module, modular type, collectors.